The influence of corporate social responsibility (CSR) on the development of business sustainability in selected private sector in Sabah - Helmina Thomas; Toh Pei Sung; Stephen Laison Sondoh Jr.; Dean Nelson Mojolou (Faculty of Business, Economics and Accountancy, 2021)
The concept of Corporate Social Responsibility has become one of the initiatives to grow business development among many companies and their partner by emphasizing their mission and vision to get closer to the community. It has a significant impact on the development of business processes that are effective and efficient while also achieving a high level of performance toward a sustainable process. Therefore, the purpose of this paper is to investigate the influence of corporate social responsibility toward developing business sustainability in the private sector in Sabah. There are three corporate social responsibility variables to be tested, namely customer, employee, and environment. For the dependent variable, the three-bottom line of business sustainability theory is used. A questionnaire was developed to obtain data from the respondent using non-probability sampling techniques, which is purposive sampling techniques. The data are collected from selected private sectors in Sabah. The result implies that there is a relationship between corporate social responsibility and business sustainability. It can be concluded that corporate social responsibility can have an influence on an organization’s sustainability. To be more competitive in business nowadays, any organization should plan an effective strategy on their corporate social responsibility to enhance their chance to maximize profit and productivity. The study finding will assist the private sector in Sabah in addressing the weakness and strengths of their corporate social responsibility program that has been implemented and serve as a foundation or set of principles for future business sustainability strategies.